2006
DOI: 10.1111/j.1365-3091.2006.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Porosity–permeability relationships in Miocene carbonate platforms and slopes seaward of the Great Barrier Reef, Australia (ODP Leg 194, Marion Plateau)

Abstract: This paper reports a series of 700 porosity–permeability analyses and supporting petrographic and sedimentologic descriptions from Early to Late Miocene carbonate strata cored on the Marion Plateau, offshore from north‐eastern Australia, during Ocean Drilling Program (ODP) Leg 194. The samples analysed are not only mainly coarse bioclastic limestones and dolomitized equivalents from platform‐top facies, but also include 79 plugs from deeper‐water slope to hemipelagic drift facies. Outstanding characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…This redistribution of porosity increased tortuosity and established the pathways available for subsequent fluid flow. High porosity values similar to those established in the Tengiz study rocks before burial are found today in Pleistocene grainstones in the Unda core, from the Bahamas (average neutron porosity values of 52% and plug porosity at , 40%; Melim et al 2001) and from the South Marion Platform off the Great Barrier Reef (porosity values between 15% and 50%; Ehrenberg et al 2006).…”
Section: The History Of the Late Visean Parasequencementioning
confidence: 60%
“…This redistribution of porosity increased tortuosity and established the pathways available for subsequent fluid flow. High porosity values similar to those established in the Tengiz study rocks before burial are found today in Pleistocene grainstones in the Unda core, from the Bahamas (average neutron porosity values of 52% and plug porosity at , 40%; Melim et al 2001) and from the South Marion Platform off the Great Barrier Reef (porosity values between 15% and 50%; Ehrenberg et al 2006).…”
Section: The History Of the Late Visean Parasequencementioning
confidence: 60%
“…Image analysis of all thin sections was conducted at the University of Miami. The entire thin section was photographed in plane light and crossed nicols, and the volume and shape of macroporosity described by macropore volume, dominant pore size and perimeter over area (PoA; Ehrenburg et al, 2006). Microporosity was calculated from both modal analysis and image analysis data by: Microporosity (%) ¼ Helium porosity (%) À macroporosity Water-oil capillary pressure was measured by centrifuge on 56 samples and steady state relative permeability measurements were made on 30 samples, from which residual oil saturation (Sor) were determined.…”
Section: Databasementioning
confidence: 99%
“…These cores are characterized by strong petrophysical heterogeneities over short vertical depth intervals, reflecting varying influence of both depositional textures and diagenesis (Ehrenberg et al, 2006b). Details regarding the units sampled and the separation of the samples into different textural classes are provided by Isern et al (2002); Ehrenberg et al (2006a). Fifteen horizontally oriented, 25 mm core-plugs were selected among the samples analysed by Ehrenberg et al (2003) (Figs.…”
Section: Samplesmentioning
confidence: 99%